2020
DOI: 10.15520/jcmro.v3i07.308
|View full text |Cite
|
Sign up to set email alerts
|

Apex Locator - Booster to Dentist : Literature Review

Abstract: Successful root canal treatment depends on thorough cleaning & shaping and 3- dimensional fluid impervious obturation of tooth within the confines of canals. To achieve this objective  the apical constriction must be detected accurately during canal preparation and precise  control over  working length  during the  procedure must  be maintained.  There are  many methods  of working length determination including  radigraphs  and electronic method(apex locator). Introduction of apex locators  have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The apex locator is another commonly used instrument for WL determination. The recent advances in apex locators have enabled more accurate and predictable estimation of WL [ 7 ]. Apex locators can find the location of apical constriction, which is the most suitable location for termination of root canal instrumentation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apex locator is another commonly used instrument for WL determination. The recent advances in apex locators have enabled more accurate and predictable estimation of WL [ 7 ]. Apex locators can find the location of apical constriction, which is the most suitable location for termination of root canal instrumentation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in apex locators have enabled more accurate and predictable estimation of WL [ 7 ]. Apex locators can find the location of apical constriction, which is the most suitable location for termination of root canal instrumentation [ 7 ]. A meta-analysis evaluated four generations of apex locators and reported that all generations were accurate enough for measurement of WL, and generation of apex locators had no significant effect on their accuracy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%